ANALISIS RASIO LIKUIDITAS TERHADAP KINERJA PERUSAHAAN PT CIKARANG LISTRINDO TBK TAHUN 2018-2020 - Octaviana Arisinta; Aldila Septiana; Evi Ulvah; Aqidatul Annisa; Camelia Mumaizah; Ela Sholehah; Ach. Hermansyah (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
The success of a company can be achieved if it has good financial performance. Financial reports are most needed to measure the company's business results and development from time to time, so that it is known to what extent the company has achieved its goals. This study aims to find out and explain the performance of the company PT Cikarang Listrindo, Tbk based on liquidity ratio analysis in the 2018-2020 period. This research method is descriptive quantitative with liquidity ratio measuring tools (quick ratio, current ratio, cash ratio and inventory to NWC). The type of data used in this study is a type of secondary data in the form of the financial reports of PT Cikarang Listrindo, Tbk for the 2018-2020 period published by the Indonesia Stock Exchange (IDX). The results of the analysis show that: the company's current ratio, quick ratio and cash ratio during the period 2018 to 2020 are in a liquid state; company performance based on inventory to net working capital in 2018 to 2019 in a liquid state, but in 2020 it will be in an ill liquid condition because its value does not meet industry standards